How leadership factors impact different entrepreneurship phases: an analysis with PLS-SEM - Aparisi-Torrijo, Sofia; Ribes-Giner, Gabriela; Chaves-Vargas, Joana-Carolina (Journal of Business Economics and Management, 2023)
This research work empirically contributes to the entrepreneurial leadership field by analysing how certain combinations of leadership factors impact entrepreneurship in both its launch and consolidation phases. Two relational models are proposed to study whether entrepreneurial leadership factors are positively related to different entrepreneurial activity process stages. The first analyses the effect on the venture’s launch and start-up phases, and the second examines the impact on the entrepreneurship consolidation stage. Utilising data from 50 countries of the Global Entrepreneurship Monitor, a quantitative partial least squares structural equation method was employed to validate the proposed models. The main conclusion was that the use of some leadership capabilities has an unequal influence on entrepreneurship during its life cycle. This study contributes to the field in two ways: we firstly show that leadership factors are contextual, and their contribution depends on the stage of the entrepreneurial process in which the activity is located; secondly, this research reveals that the development of leadership factors, such as self-efficacy, networking, vision and innovative behaviour, positively condition the start-up and launch phases of entrepreneurship. The outcomes of this research demonstrate significant theoretical and empirical implications by bridging the existing gaps in the niche of entrepreneurial leadership factors.